Development and Reproduction of a Japanese Strain of Ctenolepisma calvum (Ritter, 1910) at Room Temperature - Hiroki Watanabe; Megumi Shimada; Yoshinori Sato; Rika Kigawa (Insects, 2023)
Ctenolepisma calvum (Ritter, 1910) (Zygentoma: Lepismatidae) is a primitive wingless insect that causes damage to paper, and it is regarded as a pest of collections in museums, archives, and libraries. This species was recently discovered in Japan for the first time and may have already spread over large areas of Japan, but, currently, no information is available on the biological characteristics of C. calvum in Japan. In this study, we observed the processes of development and reproduction of C. calvum found in Japan at room temperature. Oviposition was observed from April to November, with a peak in early June. The average egg period was 56.9 days at average temperatures above 24.0 °C, and was 72.4 days at average temperatures below 24.0 °C. The 1st, 2nd, and 3rd instars lasted 4.7 days, 13.2 days, and 26.1 days on average, respectively, at average temperatures above 22.0 °C. Average instar periods were 23–28 days in 4th–7th instars and tended to increase in later instars. Instar periods also increased when the average temperature was 22.0 °C or lower. In individual rearing, the longest-living individual lived for approximately two years, up to the 15th instar. The head width grew at an approximate ratio of 1.1 per molt. First oviposition occurred at the 10th or 11th instar. Individually observed females oviposited once or twice a year, laying 6–16 eggs at one time, but females at least two years old laid 78.2 eggs per year on average in a mass-culture cage. Through this study, only females were found, and the mature females produced their progenies parthenogenetically.